Towards a Southern African English Defining Vocabulary - Hiles, Lorna (Lexikos, 2014)
Controlled defining vocabularies have been used regularly in lexicography since the 1970s. They are mostly employed in learners' and school dictionaries and have been used to ensure that the definitions are easily understood by the dictionary user, and that the words used to define a lemma are not more difficult than the lemma itself.In my experience, defining vocabularies compiled for English dictionaries for a British or American market are not entirely sufficient for southern African dictionaries. Words which would be well-known and used in southern Africa are not included in a foreign defining vocabulary.With this article, it is my intention to find methods of adapting existing defining vocabularies and to compile one that is more useful for southern African school dictionaries.A complete southern African English defining vocabulary is not part of the scope of this paper, but by providing some suggestions, I hope to make the reader realize that there is a need for a complete defining vocabulary that would cater to the needs of a southern African dictionary and its users. Further research would then be an extension of this paper into a full defining vocabulary (DV) that would be used for southern African dictionaries.